Control technique for single phase inverter photovoltaic system connected to the grid - Linda Hassaine; Mohamed Rida Bengourina (Energy Reports, 2020)
In photovoltaic system connected to the grid, the main goal is to control the power that the inverter injects into the grid from the energy provided by the photovoltaic generator. The power quality injected into the grid and the performance of the converter system depend on the quality of the inverter current control. In this paper, a control technique for a photovoltaic system connected to the grid based on digital pulse-width modulation (DSPWM) which can synchronize a sinusoidal output current with a grid voltage and control the power factor is proposed. This control is based on the single phase inverter controlled by bipolar PWM Switching and lineal current control. The electrical scheme of the system is presented. The approach is widely explained. Simulations results of output voltage and current validate the impact of this method to determinate the appropriate control of the system. A digital design of the control based on generator PWM using VHDL is proposed and implemented on Field-Programmable Gate Array "FPGA". The functional structure of this system with digital control has been validated with experimental results.
Keywords: 330; Grid connected photovoltaic system; Inverter; Control; Bipolar PWM